Modeling the universal viscoelastic response of polymer fibers - Sharma, Aakash; Kumaraswamy, Guruswamy; Thakre, Shirish (Physical Review Materials, 2018)
Polymer fibers, including natural silk and synthetic fibers, exhibit universal viscoelastic response. On stretching below yield, they show logarithmic stress decay. On unloading fibers with a glassy amorphous phase, the stress recovers. A simple phenomenological model accurately describes data from independent mechanical experiments and provides insights into the micro structural origins of the fiber response. Counter to intuition, the model indicates that it is the crystalline regions, rather than the amorphous glass, that deform first on stretching fibers at high strain rates. On holding a stretched fiber, stress decays as a consequence of relaxations in amorphous regions. Finally, unloading the fiber transfers stress from the amorphous to crystalline regions resulting in stress recovery. Model parameters correlate well with the fiber microstructure. Crystal and amorphous moduli from the model match those from x-ray diffraction. Activation energies for the temperature dependence of the peak relaxation time are similar to those reported in the literature. Thus, a simple model that invokes only crystal-amorphous coexistence can successfully model the mechanical response of a wide variety of polymer fibers.

Characterizing microvoids in regenerated cellulose fibers obtained from viscose and lyocell processes - Sharma, Aakash; Sen, Debasis; Thakre, Shirish; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Regenerated cellulose fibers are among the most widely used bio-derived materials. Currently, there is great interest in transitioning from the traditional viscose process to the more environmentally friendly lyocell process for fiber production. Differences between the characteristics of viscose and lyocell fibers can be attributed to microstructural differences that arise due to differences in the processing techniques. Here, we use small-angle scattering to characterize the microvoids in regenerated cellulose fibers that might govern the onset of mechanical failure in these. In regenerated cellulose fibers, scattering of X-rays or neutrons at small angles is largely dominated by scattering from microvoids. We demonstrate that small angle X-ray scattering (SAXS) over the q range that is typical for most commercial instruments arises from Porod scattering from the microvoid surfaces, viz., the scattered intensity scales as q(-4). Therefore, it is not possible to extrapolate this data to lower q to obtain microvoid dimensions and volume fraction. We combine SAXS with medium-resolution small-angle neutron scattering to characterize the microvoids in regenerated cellulose fibers. Specifically, we compare fibers produced using the viscose process with those from the lyocell process. For both viscose and lyocell fibers, microvoids have a high aspect ratio and are elongated in the fiber direction. Also, the volume fraction occupied by the microvoids is comparable for viscose and lyocell fibers (0.04-0.05%). However, there are differences in the microvoid size: Microvoids are more highly oriented in lyocell fibers and have a larger average length and diameter compared with viscose fibers. This result might have important implications for understanding failure of these fibers.

Structure-property relations in regenerated cellulose fibers: comparison of fibers manufactured using viscose and lyocell processes - Sharma, Aakash; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (Cellulose, 2019)
Regenerated cellulose fibers are produced using two industrially dominant technologies: the viscose and lyocell processes. Here, we compare commercially available fibers, prepared using the viscose and lyocell processes. Single fibers are subjected to a variety of mechanical deformations to obtain stress-strain, stress relaxation and stress recovery data. These are fitted to a phenomenological model, whose parameters are interpreted in terms of the fiber semicrystalline microstructure. This simple model does not incorporate the complexities of semicrystalline microstructure. Rather, it represents structure in a semicrystalline polymer fiber in terms of an elastic crystalline phase that coexists with a viscoelastic Voigt-like glassy amorphous phase. Lyocell fibers are characterized by higher values of crystalline modulus relative to viscose. Lyocell fibers also have a higher amorphous phase modulus and a wider relaxation spectrum than viscose, suggesting that amorphous and crystalline phases are dispersed in close connectivity in lyocell. Viscose and lyocell fibers exhibit qualitative similarities in their mechanical response. On stretching, there is a transition in the stress-strain curve from a low strain elastic response at a critical value of strain. This critical strain has been incorrectly attributed to yielding of the fiber. We establish that this critical value corresponds to an apparent yield. When subjected to strains higher than this apparent yield point, the fibers develop a memory of the mechanical deformation. This memory decays slowly, logarithmically with time and is lost over about a day as the fiber structure transitions back to the original as spun fiber. Finally, we demonstrate that on wetting the fibers with water, there is an increase in the apparent yield strain for viscose fibers, but not for lyocell. We interpret these results in terms of the semicrystalline microstructure of the fibers.
Keywords: mechanical properties; Model; Regenerated cellulose; Yielding

Microstructural differences between Viscose and Lyocell revealed by in-situ studies of wet and dry fibers - Sharma, Aakash; Thakre, Shirish; Kumaraswamy, Guruswamy (Cellulose, 2020)
Regenerated cellulose fibers manufactured using Lyocell and Viscose processes exhibit differences in their structural response to mechanical deformation. Here, we study the effect of stretching and stress relaxation on the orientation of crystal and amorphous phases. Our results show that on stretching, orientation in both crystal and amorphous phases increases linearly with strain, correlating with the increase in stress and with the stretching of the crystalline unit cell along the c-axis. On holding after stretching to a particular strain, the stress relaxes logarithmically in time, correlating with a decrease in the strain along the c-axis of the crystal unit cell. The stress relaxation is also correlated with a logarithmic increase in amorphous orientation, while crystalline orientation stays constant. We attribute the stress development during stretching to deformation of the crystal unit cell, while crystal reorientation in the fiber direction results in increase in the crystalline orientation parameter. On holding the fiber at a fixed total strain, the stress relaxes as strain is transferred from crystal to amorphous regions. Thus, the strain on the unit cell c-axis decreases and amorphous orientation increases. There are quantitative differences between the rate of increase in amorphous phase orientation during stress relaxation for Lyocell and Viscose fibers. For dry fibers, Lyocell shows a slower increase in orientation during stress relaxation. On wetting the fibers, their structural response changes qualitatively. We combine wide angle x ray diffraction and birefringence experiments with our model to infer that that on stretching the wet fiber, the crystalline phase is neither strained nor oriented. However, orientation develops in the amorphous phase. During stress relaxation in wet condition, Lyocell fibers shows a faster increase in amorphous orientation than Viscose fibers, in line with the comparison of relaxation time spectra for wet Viscose and Lyocell fibers. Graphic abstract
Keywords: birefringence; Crystal-amorphous orientation; In-situ WAXD; Regenerated cellulose

Process-induced microstructure in viscose and lyocell regenerated cellulose fibers revealed by SAXS and SEM of acid-etched samples - Sharma, Aakash; Wankhede, Parnashri; Samant, Roopali; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2021)
Regenerated cellulose fibers represent an important class of bioderived commercial fibers. The traditional viscose process requires the use of environmentally harmful carbon disulfide solvent to produce fibers. Lyocell fibers, produced using a more sustainable recent process, exhibit differences in properties from viscose. These differences arise from their semicrystalline microstructure, formed during fiber spinning. It is widely believed that regenerated cellulose fibers predominantly form fringed fibrillar crystals. We optimize acid etching, followed by SEM as an experimental tool to visualize this fibrillar structure. Acid etching provides sufficient topological contrast to directly visualize similar to O(10 nm) fibrils using field-emission scanning electron microscopy (SEM). We combine SEM with small-angle X-ray scattering (SAXS) to reveal other microstructural details. We observe a Bragg peak, indicating the coexistence of stacked lamellar structure with crystalline fibrils for viscose fibers, but not for lyocell. Viscose and lyocell fibers are characterized by partially oriented semicrystalline microstructure. We present a methodology to calculate the Lorentz correction for such microstructure and employ this to analyze the lamellar scattering from viscose fibers using a 1D correlation function approach. We characterize the lamellar microstructure after swelling viscose fibers with water and observe expansion of the Bragg spacing due to water absorption in the amorphous regions. Our data suggest that the water-induced plasticization of amorphous regions is inhomogeneous. Lamellar stacks that are more misoriented from the fiber direction exhibit lower swelling than those along the fiber direction. The experimental methods described in this work reveal interesting details of semicrystalline microstructure in regenerated cellulose fibers, with important implications for the mechanical response of dry and wet fibers. The methods developed here might find use in investigations of other polymer fibers as well.
Keywords: acid etching; crystalline lamellae; fibers; fibrils; Lorentz correction; Regenerated cellulose; SAXS